1990
DOI: 10.1136/thx.45.7.497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lung resection on pulmonary function and exercise capacity.

Abstract: The effects of lung resection on exercise capacity and perception of symptoms were studied in 47 patients aged 39-73 (mean 58 3) years. Twenty had a pneumonectomy and 27 a lobectomy, all for lung cancer. Forced expiratory volume, maximal inspiratory and expiratory pressures, and progressive maximal one minute incremental cycle ergometer exercise performance were measured before and after surgery. Breathlessness and leg discomfort were assessed with a modified Borg scale (0-10). Mean FEVy decreased from 79% (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
1
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 18 publications
7
59
1
3
Order By: Relevance
“…PELLETIER et al [14] found a loss in exercise capacity of 28% after pneumonectomy and 20% after lobectomy. These results are difficult to compare to ours because of their early time-point of evaluation (mean 73 days after lobectomy and 62 days after pneumonectomy) and the wide range over which it took place (26-200 days).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PELLETIER et al [14] found a loss in exercise capacity of 28% after pneumonectomy and 20% after lobectomy. These results are difficult to compare to ours because of their early time-point of evaluation (mean 73 days after lobectomy and 62 days after pneumonectomy) and the wide range over which it took place (26-200 days).…”
Section: Discussionmentioning
confidence: 99%
“…Various previous reports have analysed functional loss in PFT after lung resection. Unfortunately, the time-points of analysis were quite different in some reports, making direct comparison difficult [11,14]. We decided on 3 and 6 months evaluation postoperatively for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALI et al [115] and LODDENKEMPER et al [16] have shown that resections involving not more than one lobe lead to an early loss in pulmonary function with later recovery and little permanent deficit. As for the preoperative assessment, exercise capacity reflects the functional postoperative reserves better than simple PFT, but has been investigated much less frequently than PFT [70,124,148,149]. As early as 1965, DEGRAFF et al [70] reported on exercise limitation after extensive pulmonary resection.…”
Section: Effect Of Lung Resection On Postoperative Pulmonary Functionmentioning
confidence: 99%
“…PELLETIER et al [149] investigated 20 patients after pneumonectomy and 27 after lobectomy. The mean decrease in FEV1 was 17% after lobectomy and 31% after pneumonectomy, and the respective values for the maximal work capacity were 12 and 26%.…”
Section: Diagnosismentioning
confidence: 99%